The design and synthesis of MRI contrast agents for imaging cancer and hypoxia - Grimes, Eleanor F. (2014)
The aim of this thesis was to develop a series of gadolinium(III) contrast agents based on the DOTA and AAZTA molecules used widely in the literature that will locate preferentially in hypoxic tumour cells. Three contrast agents were synthesised with alkyne tags, by adapting compounds already produced in the literature. Whilst contrast agents in the clinic locate preferentially in cancer cells over normal tissues, they do not have the ability to inform a clinician about the type, or the environment of the cancer. One cancer environment that often leads to poor patient prognosis is hypoxia, as hypoxic tumours are both chemotherapy and radiotherapy resistant, whilst also promoting metastasis at a cellular level. Under hypoxic conditions nitro-aromatic compounds can be enzymatically reduced to either the hydroxylamine or amine compounds. Once this has occurred either a leaving group can be lost, or partial ring breakdown occurs, which can then be attacked by molecules within the cell such as glutathione to form a covalent bond. This tethers the hypoxic marker within the hypoxic cell. Currently this technology is only used with nuclear medicine techniques, whilst this thesis outlines how this principle is to be used in conjunction with MRI technology. The hypoxia markers were synthesised with azide functionalities to allow the two halves of these molecules to be conjugated using the copper (I)-catalyzed azide-alkyne cycloaddition. The conjugation occurred as the last step to produce a series of final compounds. Once synthesised these contrast agents were characterised using NMR relaxivity calculations, to prove their effectiveness as contrast agents. They were also to undergo enzymatic tests using xanthine oxidase and glutathione to see if the nitro-aromatics can be reduced under hypoxic conditions, and thus their ability to locate within the hypoxic region of a tumour. Unfortunately this last step wasn’t completed due to time constraints.